Pathogenicity of Gaeumannomyces graminis var tritici increased by nitrogen applied to soil to enhance the decomposition rate of wheat residues - van_Toor, R.F.; Butler, R.C.; Braithwaite, M.; Bienkowski, D.; Qiu, W.; Chng, S.F.; Cromey, M.G. (New Zealand Plant Protection, 2016)
Soil cores removed after harvest of a wheat crop infected with the fungus Gaeumannomyces graminis var tritici (Ggt) were amended with nitrogen and fungal saprophytes to increase decay of crop residues and subsequently reduce soil inoculum The cores were treated with one application of 50 kg nitrogen (N) per ha Trichoderma strains or both Cores were assessed 0 2 4 and 7 months after harvest At 7 months the crop residues had decayed to a third of their original mass with the decay not influenced by the treatments DNA analysis confirmed Ggt DNA was present in the stubble stems crowns and roots The pathogenicity of Ggt was increased by N as shown by a 5 to 8fold increase in takeall severity in indicator wheat seedlings planted in the Ntreated cores 2 to 4 months after harvest compared with those without N Ggt remained viable in all treatments to infect wheat seedlings 7 months after harvest